Issues Of Increasing The Role Of Investment In Agricultural Development Uzbekistan - Djumaniyazov Ubbiniyaz Ismayl Ogli (Genius Journals, 2024)
This article reveals the importance of agriculture in the development of the country's economy in a market economy and the importance of investment in its development, especially foreign investment. Investments play a fundamental role in the development of industries and regions, as well as the economy of the republic and in achieving success in the socio-economic sphere of the country. Therefore, the ways of creating a favorable investment climate for attracting foreign investment and efficient use of internal reserves are shown.
Keywords: Modernization; foreign investment; financial resources